Analysis Of Structure And Sentence Types in The News Detik.Com Sumut 'Case of Electric Outages in Medan City' - Aulia Rahma; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2024)
This research aims to analyze the types of sentences used in the news entitled